Efeitos do consumo da multimistura sobre o estado nutricional: ensaio comunitário envolvendo crianças de uma favela da periferia de Maceió, Alagoas, Brasil Effects of the consumption of "multimixture" on nutritional status: a community trial involving children from a slum district on the outskirts of Maceió, State of Alagoas, Brazil - Haroldo da Silva Ferreira; Sybelle de Araújo Cavalcante; Cyro Rego Cabral Jr; Adriana Toledo de Paffer (Instituto Materno Infantil de Pernambuco, 2008)
OBJETIVOS: verificar o impacto do consumo da multimistura sobre as condições de nutrição e saúde de crianças em situação de risco. MÉTODOS: ensaio comunitário envolvendo crianças (6 a 60 meses) de uma favela de Maceió, Alagoas, Brasil, aleatoriamente alocadas para o Grupo Controle (n=50) ou Grupo Multimistura (n=48). Neste, a suplementação consistiu de duas colheres de sopa/dia. Avaliações antropométricas foram realizadas antes e após a fase experimental (10 meses). A incidência de agravos à saúde foi investigada pela realização de inquéritos quinzenais de morbidade. O consumo alimentar foi ana-lisado por inquérito recordatório de 24 horas (três dias alternados). Os níveis de hemoglobina (Hemocue ) e de retinol sérico (HPLC) foram aferidos apenas no final da fase experimental. As medidas de desfecho foram comparadas entre os grupos usando-se testes paramétricos ou não-paramétricos, conforme cada situação. Diferenças foram consideradas como estatisticamente significativas quando p<0,05. RESULTADOS não foram observadas diferenças (p>0,05) entre os resultados obtidos na avaliação antropométrica, dietética, bioquímica e na incidência de diarréia, vômitos e febre. Todavia, as infecções respiratórias incidiram de forma mais intensa sobre as crianças do Grupo Controle (24,3% vs. 16,9%; OR=1,59; IC95%=1,13-2,24; p<0,01). CONCLUSÕES: a suplementação com multimistura não alterou o perfil antropométrico ou a freqüência de anemia e hipovitaminose A entre as crianças. OBJECTIVES: to investigate the impact of the consumption of "multimixture" (a bran-based cereal mixture) on the nutritional status of children at risk of malnutrition. METHODS: a community trial involving children (6 to 60 months) from a slum area in the city of Maceió, State of Alagoas, Brazil, randomly assigned to the Control Group (n=60) or to the "multimixture" Group (n=48). The supplement consisted of two tablespoons of "multimixture" per day. Anthropometric measurements were taken before and after the experimental phase (10 months). The incidence of health problems was investigated on a biweekly basis. Food consumption was assessed by way of 24 hour dietary recall (on three alternate days). Hemoglobin (HemoCue®) and serum retinol (HPLC) were determined at the end of the experimental phase. The resulting measurements for the two groups were compared using parametric or non-parametric statistics in according with the situation. Differences were considerate as significative statistically when p<0.05. RESULTS: no differences were observed (p>0.05) between the results obtained from anthropometric measurements and dietary intake, between levels of hemoglobin and serum retinol or in the incidence of diarrhea, vomiting or fever. However, there was a higher incidence of respiratory infections among the children in the Control Group (24.3% vs.16.9%; OR=1.59; 95%CI = 1.13-2.24; p<0.01). CONCLUSIONS: the "multimixture" food supplement did not alter the anthropometric profile or the frequency of anemia or hypervitaminosis A among the children.